2023
DOI: 10.1001/jama.2023.19524
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine Compound (Tongxinluo) and Clinical Outcomes of Patients With Acute Myocardial Infarction

Yuejin Yang,
Xiangdong Li,
Guihao Chen
et al.

Abstract: ImportanceTongxinluo, a traditional Chinese medicine compound, has shown promise in in vitro, animal, and small human studies for myocardial infarction, but has not been rigorously evaluated in large randomized clinical trials.ObjectiveTo investigate whether Tongxinluo could improve clinical outcomes in patients with ST-segment elevation myocardial infarction (STEMI).Design, Setting, and ParticipantsRandomized, double-blind, placebo-controlled clinical trial was conducted among patients with STEMI within 24 ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…In Reply In their letter to the editor, Drs Asham and Entezari-Maleki inquire about the TIMI and GRACE risk scores of patients enrolled in our recent study on Tongxinluo . The Table shows the similarity in the distribution of TIMI and GRACE scores at baseline, and the benefit of Tongxinluo in 30-day major adverse cardiac and cerebrovascular events across low-, intermediate-, and high-risk subgroups (all P values for interaction > .05).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Reply In their letter to the editor, Drs Asham and Entezari-Maleki inquire about the TIMI and GRACE risk scores of patients enrolled in our recent study on Tongxinluo . The Table shows the similarity in the distribution of TIMI and GRACE scores at baseline, and the benefit of Tongxinluo in 30-day major adverse cardiac and cerebrovascular events across low-, intermediate-, and high-risk subgroups (all P values for interaction > .05).…”
mentioning
confidence: 99%
“…In response to the letter by Dr Zakiev and colleagues about the stability of the effect of Tongxinluo, the ultra-performance liquid chromatography fingerprint for 10 different batches of Tongxinluo capsules was provided in eFigure 1 of Supplement 2 of the article . This eFigure showed the stability of the Tongxinluo capsule ingredients…”
mentioning
confidence: 99%
“…To the Editor A recent article reported a positive effect of a traditional Chinese drug (Tongxinluo) on outcomes of patients with acute myocardial infarction. Tongxinluo is a mixture of powders and extracts from multiple plant and insect products, so the concentration of active components may vary.…”
mentioning
confidence: 99%
“…To the Editor The China Tongxinluo Study for Myocardial Protection in Patients With Acute Myocardial Infarction (CTS-AMI) recently showed that the Chinese traditional medicine Tongxinluo significantly improved both 30-day and 1-year clinical outcomes of patients with acute ST-segment elevation myocardial infarction (STEMI). However, we are concerned that patient risk stratification was not included in this study.…”
mentioning
confidence: 99%
“…Although the CTS-AMI study reported prognostic risk factors of mortality in STEMI, such as age, sex, diabetes, hypertension, and medications (aspirin, angiotensin-converting enzyme inhibitors, statins, and β-blockers), its omission of risk stratification may have affected the study results because these tools are necessary to choose the best STEMI treatment modalities based on the guidelines …”
mentioning
confidence: 99%